Psychotic experiences and risk of self-injurious behaviour in the general population: a systematic review and meta-analysis. Issue 2 (30th September 2015) - Honings, S.; Drukker, M.; Groen, R.; van Os, J.
Abstract : Background: Recent studies suggest that psychotic experiences (PE) in the general population are associated with an increased risk of self-injurious behaviour. Both the magnitude of this association and the level of adjustment for confounders vary among studies. A meta-analysis was performed to integrate the available evidence. The influence of possible confounders, including variably defined depression, was assessed. Method: A systematic review and meta-analysis was conducted including general population studies reporting on the risk of self-injurious behaviour in individuals with PE. Studies were identified by a systematic search strategy in Pubmed, PsycINFO and Embase. Reported effect sizes were extracted and meta-analytically pooled. Results: The risk of self-injurious behaviour was 3.20 times higher in individuals with PE compared with those without. Subanalyses showed that PE were associated with self-harm, suicidal ideation as well as suicidal attempts. All studies had scope for considerable residual confounding; effect sizes adjusted for depression were significantly smaller than effect sizes unadjusted for depression. In the longitudinal studies, adjustment for psychopathology resulted in a 74% reduction in excess risk. Conclusions: PE are associated with self-injurious behaviour, suggesting they have potential as passive markers of suicidality. However, the association is confounded and several methodological issues remain, particularly how to separate PE from the full range of connected psychopathology in determining any specific association with self-injurious behaviour. Given evidence that PE represent an indicator of severity of non-psychotic psychopathology, the association between PE and self-injurious behaviour probably reflects a greater likelihood of self-injurious behaviour in more severe states of mental distress.